2016
DOI: 10.7771/2157-9288.1129
|View full text |Cite
|
Sign up to set email alerts
|

Building Up STEM: An Analysis of Teacher-Developed Engineering Design-Based STEM Integration Curricular Materials

Abstract: Improving K-12 Science, Technology, Engineering, and Mathematics (STEM) education has a priority on numerous education reforms in the United States. To that end, developing and sustaining quality programs that focus on integrated STEM education is critical for educators. Successful implementation of any STEM program is related to the curriculum materials used. Educators increasingly recognize the challenge of finding quality curriculum materials for integrated STEM education. In this study, 48 teachers partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 27 publications
(43 reference statements)
5
109
1
6
Order By: Relevance
“…This unit was designed to address the concepts and pedagogies identified in the STEM Integration Curriculum Assessment, STEM-ICA (Guzey, Moore, & Harwell, 2016;Moore, Guzey, & Brown, 2014). The STEM-ICA is a tool that operationalizes the STEM Integration Framework to be useful in curriculum development and assessment.…”
Section: Development Of the Integrated Stem Unitmentioning
confidence: 99%
“…This unit was designed to address the concepts and pedagogies identified in the STEM Integration Curriculum Assessment, STEM-ICA (Guzey, Moore, & Harwell, 2016;Moore, Guzey, & Brown, 2014). The STEM-ICA is a tool that operationalizes the STEM Integration Framework to be useful in curriculum development and assessment.…”
Section: Development Of the Integrated Stem Unitmentioning
confidence: 99%
“…There were two data sources for this phase of integration, observer field notes and the modified STEM-ICA tool (Guzey et al 2016). Our summative content analysis of the observer field notes indicated that the enactment of the Hexbug activity was implemented in all 10 classrooms, with all three members of each of the triads co-teaching the lesson.…”
Section: Stem Integration Phase Three: Enactment Of Lessonmentioning
confidence: 99%
“…Third, data was collected as the triads enacted the design lesson. Data from the enacted engineering design lessons included field notes from one or two observers (that were part of the larger research project team) and completion of a modified STEM Integration Curriculum Assessment (STEM-ICA) tool developed by Guzey et al (2016). This modified STEM-ICA tool consists of seven specific items that are closely aligned with what has been suggested in the framework for STEM integration in the classroom ) as important considerations for integrated STEM lessons and curriculum.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the nation seems to be orienting toward a new emphasis on engineering education for K-12 students, there is not one single definition or orientation towards what that should entail. Moreover, while some significant assessment work has been accomplished in engineering education to date (Guzey, Moore, & Harwell, 2016;Marra & Bogue, 2006;Marra, Rodgers, Shen, & Bogue, 2009, 2012National Research Council, 2001;Olds, Moskell, & Miller, 2005;Purzer, Douglas, Folkerts, & Williams, 2017;, there are still many opportunities for assessments to be developed for pre-college populations, and many states have begun to adopt the NGSS. In particular, mechanistic reasoning is an area where limited assessment work has been accomplished to date.…”
Section: Introductionmentioning
confidence: 99%